2023
DOI: 10.3390/nu15112503
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran: From Waste to Nutritious Food Ingredients

Abstract: Rice (Oryza sativa L.) is a principal food for more than half of the world’s people. Rice is predominantly consumed as white rice, a refined grain that is produced during the rice milling process which removes the bran and germ and leaves the starchy endosperm. Rice bran is a by-product produced from the rice milling process, which contains many bioactive compounds, for instance, phenolic compounds, tocotrienols, tocopherols, and γ-oryzanol. These bioactive compounds are thought to protect against cancer, vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 158 publications
0
6
0
Order By: Relevance
“…Rice bran is, in fact, a by-product of rice milling and is generally used as an animal feed ingredient or as raw material for the production of fertilizers [53]. However, it has potential for being valorised because it is a good source of dietary fibre, vitamins, minerals, protein, lipids, and some phytochemicals such as ferulic acid, γ-oryzanol, and tocopherol [54].…”
Section: Bio-production Of Mixtures Of Aroma Compoundsmentioning
confidence: 99%
“…Rice bran is, in fact, a by-product of rice milling and is generally used as an animal feed ingredient or as raw material for the production of fertilizers [53]. However, it has potential for being valorised because it is a good source of dietary fibre, vitamins, minerals, protein, lipids, and some phytochemicals such as ferulic acid, γ-oryzanol, and tocopherol [54].…”
Section: Bio-production Of Mixtures Of Aroma Compoundsmentioning
confidence: 99%
“…In 2021, the global rice production was 787 million metric tons, with approximately 80 million tons of rice bran being generated [ 1 ]. Traditionally, rice bran was considered an agricultural waste with only limited usage as animal feed [ 2 ]. Disposing such a high volume of industrial food residuals is a substantial undertaking and, without proper management, can pose significant environmental and public health issues [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Disposing such a high volume of industrial food residuals is a substantial undertaking and, without proper management, can pose significant environmental and public health issues [ 3 ]. Consequently, much research has been devoted to finding sustainable ways to recycle and reuse rice bran, most notably as a functional and nutritional food ingredient, by leveraging on the many bioactive compounds, such as phenolics, tocotrienols, tocopherols, and γ-oryzanol [ 2 ]. Moreover, rice bran is also a rich source of dietary fibre, comprising 8.5% arabinoxylans, which acts as a prebiotic for promoting gut health through stimulating beneficial gut microbial species to improve immune health and prevent chronic disease [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Suttiaporn et al [2] demonstrated the anti-leukemic cell activity of phytosterols and triterpenoids isolated from black rice bran. A review by Tan et al [3] suggests that bioactive compounds from rice bran waste produced during the milling process, which removes the bran and germ and leaves the starchy endosperm, can benefit nutrition and health. Although thermal cooking decreases anthocyanin content and antioxidative activity, it does not affect the anti-inflammatory activity of black rice [4].…”
Section: Introductionmentioning
confidence: 99%